GPR15-mediated T cell recruitment during acute viral myocarditis is associated with improved virus elimination and outcome. (10th June 2022) - Stoffers, B; Bacmeister, L; Braeuninger, H; Warnke, S; Brehm, M; Kim, S; Yan, I; Becher, M; Escher, F; Klingel, K; Zeller, T; Kirchhof, P; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): DZHK Ernst und Berta Grimmke Stiftung Background: Myocarditis is an inflammatory disease of the myocardium indicated by mononuclear cell infiltration. It is predominantly caused by infectious agents such as coxsackievirus B3 (CVB3). Especially in young adults, myocarditis is a major source of sudden cardiac arrest. However, its clinical course has a broad spectrum of outcomes, ranging from mild symptoms and complete recovery to cardiac dysfunction and dilated cardiomyopathy. G protein-coupled receptor 15 (GPR15) was identified as a T cell homing receptor in the context of inflammatory intestine and skin diseases. We found Gpr15 to be highly upregulated in the left ventricle (LV) 7 days after CVB3 infection in wild type (WT) mice. Purpose: GPR15 has not been described in a cardiac context, yet. Our aim was to investigate the role of GPR15 in recruiting immune cell subsets and later in virus elimination during viral myocarditis. Methods: Gpr15 deficient (Gpr15gfp/gfp) and WT mice were infected intraperitoneal with CVB3 to investigate the acute (6 & 7 days post infection(p.i.)) and the subacute phase (16 days p.i.) of myocarditis. To study differentially expressed genes, LV tissue was used for TaqMan analysis and RNA-sequencing. Inflammation and fibrosis were evaluated on histological level. For functional characterization, healthy and diseased mice were hemodynamically characterized 16 days p.i.. Furthermore, in vitro migration assays were used to study the interaction between GPR15 and its ligands in vitro. Results: Infected Gpr15gfp/gfp mice exhibited higher upregulation of immune response related genes on mRNA level in the acute phase of myocarditis 7 days p.i.. For instance, Cd8a, a cytotoxic T cell marker, and Foxp3, a regulatory T cell marker, were significantly higher in infected Gpr15gfp/gfp compared to infected WT mice. Bulk RNA-sequencing confirmed that the response to virus did not decline from day 6 to 7 in infected GPR15-deficient mice as observed in infected WT mice. Subsequent gene ontology (GO) term analyses reveled enhanced chemotaxis and cytotoxic T cell-related GO terms in GPR15-deficient mice on day 7. Among investigated T cell subsets, GPR15 was highest expressed on CD8+ T cell. Its deficiency abolished chemotaxis of T cells, especially of cytotoxic T cells, towards GPR15 ligand in vitro. In the subacute phase of myocarditis 16 days p.i., viral persistence was observed in more than 85 % of Gpr15gfp/gfp mice. In contrast, more than 70 % of WT mice with verified viremia cleared the virus successfully. Furthermore, Gpr15gfp/gfp mice demonstrated a decreased cardiac function accompanied by increased fibrosis in comparison to WT mice. Conclusion: Our findings indicate that despite the prolonged inflammatory response, scant virus elimination was presumably caused by decelerated recruitment of cytotoxic T cells leading to impaired outcome in the GPR15-deficient mice.